Defecography: a still needful exam for evaluation of pelvic floor diseases - Gazzani, Silvia Eleonora; Marcantoni, Emanuela Angela; Capretti, Giovanni; Trunfio, Vincenzo; Bacchini, Emanuele; Artioli, Giulia; Paladini, Ilaria; Seletti, Valeria; Milanese, Gianluca; Barbalace, Sandro; Borgia, Daniele; Bresciani, Paolo (Acta Biomedica Atenei Parmensis, 2016)
The aim of this discussion is to describe what is a defecography, how we have to perform it, what can we see and to present the main physio-pathological illnesses of pelvic floor and anorectal region that can be studied with this method and its advantages over other screening techniques. Defecography is a contrastographic radiological examination that highlights structural and functional pelvic floor diseases. Upon preliminary ileum-colic opacification giving to patient radiopaque contrast, are first acquired static images (at rest, in maximum voluntary contraction of the pelvic muscles, while straining) and secondarily dynamic sequences (during evacuation), allowing a complete evaluation of the functionality of the anorectal region and the pelvic floor. Defecography is an easy procedure to perform widely available, and economic, carried out in conditions where the patient experiences symptoms, the most realistic possible. It can be still considered reliable technology and first choice in many patients in whom the clinic alone is not sufficient and it is not possible or necessary to perform a study with MRI